2010
DOI: 10.1111/j.1743-6109.2010.01999.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging of Love: fMRI Meta-Analysis Evidence toward New Perspectives in Sexual Medicine

Abstract: Introduction. Brain imaging is becoming a powerful tool in the study of human cerebral functions related to close personal relationships. Outside of subcortical structures traditionally thought to be involved in reward-related systems, a wide range of neuroimaging studies in relationship science indicate a prominent role for different cortical networks and cognitive factors. Thus, the field needs a better anatomical/network/whole-brain model to help translate scientific knowledge from lab bench to clinical mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
88
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 77 publications
(176 reference statements)
5
88
1
Order By: Relevance
“…Although safety-signaling processes may overlap to some extent with reward-related processes, because cues of safety may be intrinsically rewarding or reinforcing (16,32), several points are inconsistent with the conclusion that the processes observed in the current study are simply the result of the rewarding experience associated with viewing partner pictures. Earlier studies have shown that viewing romantic partners (without receiving pain) activates the caudate and ventral tegmental area but not the VMPFC (34)(35)(36)(37)(38). In fact, in the current study, viewing attachment figures during pain led to reduced, rather than increased, activity in the caudate-a pattern inconsistent with the notion that the effects reported here are simply the result of the rewarding experience of viewing partner pictures.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although safety-signaling processes may overlap to some extent with reward-related processes, because cues of safety may be intrinsically rewarding or reinforcing (16,32), several points are inconsistent with the conclusion that the processes observed in the current study are simply the result of the rewarding experience associated with viewing partner pictures. Earlier studies have shown that viewing romantic partners (without receiving pain) activates the caudate and ventral tegmental area but not the VMPFC (34)(35)(36)(37)(38). In fact, in the current study, viewing attachment figures during pain led to reduced, rather than increased, activity in the caudate-a pattern inconsistent with the notion that the effects reported here are simply the result of the rewarding experience of viewing partner pictures.…”
Section: Discussioncontrasting
confidence: 99%
“…Although we do not view safety-signaling processes as being incompatible with reward-related processes, because cues of safety may themselves be experienced as rewarding (16,32), it is important to explore whether the current task activates neural regions that are more common to studies of safety signaling or more common to studies exploring the rewarding experience of viewing partner pictures. Specifically, research on safety-signaling and fear-extinction processes typically have yielded VMPFC activity without other reward-related regions such as the ventral striatum (11)(12)(13)(14) and have shown that the ventral striatum is not needed for safety-signaling processes (33) On the other hand, previous work on viewing romantic partners has led to increased activity in dopamine-rich reward-related regions, such as the caudate and ventral tegmental area, but not to activity in the VMPFC (34)(35)(36)(37)(38). Thus, exploring the pattern of neural activity associated with viewing attachment figures during pain would help determine if this experience is more closely aligned with safetysignaling processes or more closely aligned with the potentially rewarding experience of viewing partner pictures.…”
mentioning
confidence: 99%
“…This age group practiced sport mostly over a period of 30 minutes to one hour.The results of the study conducted by researchers at the University of California with 95sedentary men aged on average 48years old, healthy, trained four times a week and 60 minutes per session at an intensityrepresenting up to 80% of their maximum heart capacity, however revealed that these men had an increase of 30% of their sexual relations [19]. The lack of increase in the number of intercourse in subjects aged more than 45 years could be justified by the fact that they have a lower session time than that stated in the study above.The rate of increase of the refractory period is on average higher among practitioners of health sport than in sportsmen.…”
Section: Discussionmentioning
confidence: 99%
“…During the past 40 years, several studies have reinforced this psychological definition of love, and concluded that "love is more than a basic emotion. Love is a rewarding emotional state that includes basic emotions and also complex emotions, goal-directed motivations, and cognition" (Bianchi-Demicheli et al, 2006;Cacioppo et al, 2012;Ortigue et al, 2010). Along these lines, passionate love is defined as "a state of intense longing for union with another that is characterized by a motivated and goaldirected mental state" .…”
Section: Definition Of Lovementioning
confidence: 99%
“…Thus, companionate love is often described as friendship love and involves shared values, deep attachment, long-term commitment, and intimacy (Hatfield and Rapson, 1996). Although passionate love and companionate love may be experienced in concert, they are two different states (Ortigue et al, 2010).…”
Section: Definition Of Lovementioning
confidence: 99%